Controlled query evaluation over lightweight ontologies - Grau, BC; Kharlamov, E; Kostylev, EV; Zheleznyakov, D (CEUR-WS.org, 2014)
We study confidentiality enforcement in ontologies under the Controlled Query Evaluation (CQE) framework. In a CQE system, a policy specifies the sensitive information, and a censor ensures that answers to user's queries that could violate the policy are not returned. Our goal is the design of optimal CQE algorithms, which ensure confidentiality while maximising access to information. We study two natural classes of censors that can be realised using existing infrastructure for query answering and propose optimal CQE algorithms for the standardised profiles of the ontology language OWL 2.